Molecular Epidemiology Of Salmonella Enterica Subspecies Enterica Serovar Typhi Isolates From Kelantan Using Random Amplified Polymorphic Dna And Single Nucleotide Polymorphism - Ja’afar, Ja’afar Nuhu (2014)
Typhoid fever is an acute systemic infection of humans caused by Salmonella enterica subspecies enterica serovar Typhi (S. Typhi). Typhoid fever is endemic in Kelantan, a North-eastern state in Peninsular Malaysia. In spite of extensive intervention by the state‘s Public Health Department, outbreaks of typhoid fever continue to occur with the emergence of multi-drug resistant strains. An important strategy to eradicate this persistent disease is to identify the sources and distribution of infection; and for this, a reliable S. Typhi fingerprinting method is needed. Confirmation of the bacteria by phenotypic techniques is difficult due to the vast number of serovars (>1,500) within the subspecies enterica. Current molecular typing methods offer very high discriminatory resolutions; however, the majority are limited in identifying phylogenetic relationships, evolutionary trends or genotypic characteristics. Thus, the main objective of this study was to investigate the effect of nucleotide sequence variations in S. Typhi in relation to its phylogenetic diversity, and to identify possible epidemiological markers for easy identification and confirmation of this pathogen. Two methods were used in this study.